Threats to international financial stability - Portes, Richard; Swoboda, Alexander K.; International Center for Monetary and Banking Studies (Cambridge : New York : Cambridge University Press, 1987)
The book is the proceedings of an international conference held in Geneva, September 11-13, 1986 and organized by the International Center for Monetary and Banking Studies. This examines debt crisis, pace of financial innovation, policy conflicts among major industrialized countries, variability of exchange rates and interest rates etc. how they constitute a threat to international financial stability.
Includes index.
Includes bibliographies
usc 09/04/18
Loans
Keywords: International finance